Refining Expertise : How Responsible Engineers Subvert Environmental Justice Challenges - Ottinger, Gwen (Book collections on Project MUSE., 2013)
Residents of a small Louisiana town were sure that the oil refinery next door was making them sick. As part of a campaign demanding relocation away from the refinery, they collected scientific data to prove it. Their campaign ended with a settlement agreement that addressed many of their grievances--but not concerns about their health. Yet, instead of continuing to collect data, residents began to let refinery scientists' assertions that their operations did not harm them stand without challenge. What makes a community move so suddenly from actively challenging to apparently accepting experts' authority? Refining Expertise argues that the answer rests in the way that refinery scientists and engineers defined themselves as experts. Rather than claiming to be infallible, they began to portray themselves as responsible . This work drives home the need for both activists and politically engaged scholars to reconfigure their own activities in response, in order to advance community health and robust scientific knowledge about it.